FABRIKASI ARANG AKTIF TEMPURUNG KELAPA, ARANG AKTIF ALEURITES MOLUCCANA DAN KARAKTERISASINYA - Alfrie Rampengan; Vicky Mawuntu (Jurnal Kimia Fullerene, 2022)
Utilization of coconut and candlenut plants in Indonesia is still limited to the utilization of the fruit flesh, so that the waste resulting from the use of coconuts, namely the shell, has not been utilized optimally, especially in North Sulawesi. The aim of this study was to look at the functional groups in the activated carbon of coconut shell charcoal and aleirites moluccana (pecan shell) charcoal using Fourier Transform Infra Red (FTIR). The results of this study showed that the activated carbon of coconut shell charcoal and aleirites moluccana (pecan shell) charcoal had functional groups O-H, C=C, C-O, C-H. This group is an arrangement that belongs to an activated carbon.